Sistem Pengambilan Keputusan terhadap Kinerja Karyawan Berdasarkan Usia Menggunakan Metode AHP dan MOORA di Lonsum Perkebunan Pulo Rambung Estate Divisi IV - Yani, Sri Suci; Hasugian, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Companies are required to work more effectively and efficiently due to increasingly tight company competition. If employee performance increases, the quality of the company will also increase. One form of motivation and appreciation from the company is providing performance appraisals for employees. By having employees who excel and have high loyalty to the company, the company can develop and progress rapidly. By selecting the best employees you can improve employee performance. Therefore, standardization or criteria for assessing employee performance. In oil palm plantations there are positions or job positions which are determined based on the age and productivity of the employee, because this work requires a lot of energy. This research is to develop a SPK which is expected to provide an accurate decision, and based on agreed criteria by combining two methods, namely where the AHP calculates the level of importance of the weights for each criterion and sub-criteria. Furthermore, the MOORA method functions to rank by comparing the value of each criterion for each alternative. By assessing employee performance, employee performance can be motivated and appreciated so that it can improve the quality of employee work. This research uses 7 assessment criteria using 25 employee data, so that it gets the largest optimization value, namely 10.2065 with rank 1 aged 53 years and A24 gets the smallest optimization, namely 5.7236 with rank 25 aged 36 years.